miR-425-5p, a SOX2 target, regulates the expression of FOXJ3 and RAB31 and promotes the survival of GSCs - Rocha, Arlet María Acanda de la; González-Huarriz, Marisol; Guruceaga, Elizabeth; Mihelson, Nicole; Tejada-Solís, Sonia; Díez-Valle, Ricardo; Martínez-Vél, Naiara (Archives of Clinical and Biomedical Research, 2020)
Glioblastoma (GBM) is the most common malignant primary brain tumor in adults and prognosis is poor despite maximum therapeutic efforts. GBM is composed of heterogeneous cell populations, among which the glioma stem-like cells (GSCs) play an important role in tumor cell self-renewal and the ability to initiate and drive tumor growth and recurrence. The transcription factor SOX2 is enriched in GSCs where it controls the stem cell phenotype, invasion and maintenance of tumorigenicity. Therefore, understanding the molecular mechanisms governed by SOX2 in GSCs is crucial to developing targeted therapies against this resistant cell population. In this study, we identified and validated a miRNA profile regulated by SOX2 in GSCs. Among these miRNAs, miR-425-5p emerged as a significant robust candidate for further study. The expression of miR- 425-5p was significantly enriched in clinical GBM specimens compared with a human brain reference sample and showed a positive correlation with SOX2 expression. Using a combination of in silico analyses and molecular approaches, we show that SOX2 binds to the promoter of miR-425-5p. Loss of function studies show that repressing miR-425-5p expression in multiple GSCs inhibited neurosphere renewal and induced cell death. More importantly, miR-425-5p inhibition extended survival in an orthotopic GBM mouse model. Finally, combining several bioinformatics platforms with biological endpoints in multiple GSC lines, we identified FOXJ3 and RAB31 as high confidence miR-425-5p target genes. Our findings show that miR-425-5p is a GBM stem cell survival factor and that miR-425-5p inhibition function is a potential strategy for treating GBM.